Significance of free to total PSA ratio in men with normal digital rectal examination, normal transrectal ultrasonography, and intermediate total serum PSA levels - (:unkn) unknown (My University, 2001)
Purpose: To investigate the value of free to total prostate specific antigen (PSA) ratio in the detection of prostate cancer (Pca) in patients with intermediate total PSA levels (4-10 ng/ml), normal digital rectal examination (DRE) and normal transrectal ultrasonography (TRUS). Patients and methods: A total of 94 patients with normal DRE and TRUS, who attended the outpatient urology department with lower urinary tract symptoms underwent TRUS-guided systemic and lesion-directed biopsies due to intermediately elevated total PSA levels (4-10 ng/ml). Results: Histopathological examination revealed 23 (24.4%) cases with Pca. Cancer detection ratio was 1/4 biopsies based on total PSA levels between 4-10 ng/ml. Considering the free to total PSA ratio (cutoff ratio 0.15), 41 patients were below 0.15 and 18 (44%) of them had Pca. Thus, 53 biopsies would be avoided, while 21.7% (5/23) of cancer cases would have been missed. The cancer detection ratio was 1/2.2 biopsies, based on the free to total PSA ratio <0.15. On the other hand, taking 0.10 as the cutoff level of the free to total PSA ratio, there were 14 patients and 11(78.6%) of them had Pca. But in this way 52% (12/23) of cancer cases would have been missed. Conclusion: Free to total PSA ratio alone would spare unnecessary biopsies at the expense of missing at least 20% of Pca cases. Therefore, according to our results, distinct use of free to total PSA ratio should not be advised as a biopsy indicator.
Keywords: Free to total PSA ratio; Prostate cancer; Prostate specific antigen